2017
DOI: 10.1007/s10695-017-0400-1
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of enzyme-treated soy protein saves dietary protein and promotes digestive and absorptive ability referring to TOR signaling in juvenile fish

Abstract: This study was conducted to evaluate the effect of enzyme-treated soy protein (ETSP) supplementation in the low-protein diet on growth performance, digestive and absorptive capacities, and related signaling molecules' gene expressions in juvenile Jian carp. The results showed that percent weight gain (PWG), specific growth rate (SGR), and feed intake (FI) were decreased by reducing dietary protein from 34 to 32% (P < 0.05). Supplying low-protein diet with optimal ETSP increased previously mentioned indices of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…This study used the same growth trial as in our previous study, which observed that adding optimal level of ETSP to the low‐protein diet improved the growth of juvenile Jian carp (the final mean weight and SD of groups 1–7 are 86.67 ± 2.70 b , 82.22 ± 2.01 a , 86.81 ± 2.43 b , 89.69 ± 2.61 b , 87.58 ± 2.27 b , 86.53 ± 3.79 b , 85.39 ± 2.12 ab g respectively), and promoted digestive and absorptive ability referring to TOR signalling in juvenile fish, showing that 1% of ETSP (only provided 0.46% crude protein) can save 2% of dietary crude protein (Xiao et al, ). Our laboratory's previous study showed that the digestion and absorption function mainly rely on the intestinal health in aquatic animals, which has been found to be correlated with the intestinal immunity and structure (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study used the same growth trial as in our previous study, which observed that adding optimal level of ETSP to the low‐protein diet improved the growth of juvenile Jian carp (the final mean weight and SD of groups 1–7 are 86.67 ± 2.70 b , 82.22 ± 2.01 a , 86.81 ± 2.43 b , 89.69 ± 2.61 b , 87.58 ± 2.27 b , 86.53 ± 3.79 b , 85.39 ± 2.12 ab g respectively), and promoted digestive and absorptive ability referring to TOR signalling in juvenile fish, showing that 1% of ETSP (only provided 0.46% crude protein) can save 2% of dietary crude protein (Xiao et al, ). Our laboratory's previous study showed that the digestion and absorption function mainly rely on the intestinal health in aquatic animals, which has been found to be correlated with the intestinal immunity and structure (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate product after enzyme hydrolysis was dried at 90°C for 12 hr. Proximate composition and peptide profile of ETSP were quoted from Xiao et al () providing in Table .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations